(untitled) (Ustozlar uchun, 2024)
Abctract. To date, along with many developing sectors in our country, the transport sector is developing rapidly. Air, water and land transport, which are its main branches, are gaining importance in the development of our country's economy. This article describes in detail the main types of transport in our country.